Development and optimization of sorghum-flakes based nutribar for physcio-chemical and organoleptic evaluation - Joshi, Priti T; Sadawarte, S K; Pawar, V S (Journal of Cereal Research, 2023)
Nutribar is a highly nutritious snack food that can be prepared using variety of ingredients as cereals, legumes, oilseed and many more. Flakes based bar now becoming popular due to its nutritional value and ease of availability. The present study was conducted for standardize the procedure for preparation of sorghum flakes based nutribar and its optimization for sensory parameters and proximate composition. Nutribar formulated using sorghum flakes, rice flakes, sesame, peanut, jaggery and liquid glucose. The findings revealed that nutribar with 20% sorghum flakes and 10% rice flakes were highly acceptable. Prepared bar was rectangular in shape, weight, length and width of all samples were found to be almost same. Further the proximate composition was assessed and found that protein content ranged from (13.51 -14.42%), carbohydrate (62.51-63.59%) and crude fiber ranged from (5.61-6.34%).